2006
DOI: 10.1302/0301-620x.88b11.17424
|View full text |Cite
|
Sign up to set email alerts
|

Does the method of treatment affect the outcome in soft-tissue sarcomas of the adductor compartment?

Abstract: We have investigated the significance of the method of treatment on the oncological and functional outcomes and on the complications in 184 patients with soft-tissue sarcomas of the adductor compartment managed at three international centres. The overall survival at five years was 65% and was related to the grade at diagnosis and the size of the tumour. There was no difference in overall survival between the three centres. There was, however, a significant difference in local control with a rate of 28% in Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
3
15
1
Order By: Relevance
“…Results of both studies are comparable to those reporting sarcomas in other anatomic regions. 14 The rate of major complications in our study (26%) was lower than in others (36% 7 and 43% 8 ). Nonetheless, comparisons should be interpreted with caution, as the grading system for complications was not the same.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Results of both studies are comparable to those reporting sarcomas in other anatomic regions. 14 The rate of major complications in our study (26%) was lower than in others (36% 7 and 43% 8 ). Nonetheless, comparisons should be interpreted with caution, as the grading system for complications was not the same.…”
Section: Discussioncontrasting
confidence: 69%
“…Wound complications after resections are frequent and can afflict up to 36% of the patients. 1,7,8 We reviewed outcomes and complications of 25 consecutive patients with soft tissue sarcomas in the adductor compartment. 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the outcome of patients with STS indeed does differ even among international highvolume centers. 26,27 In conclusion the presented results support our hypothesis that preoperative IMRT may lead to a reduction of wound complication rates compared to that after postoperative and mainly preoperative non-IMRT techniques.…”
Section: Discussionsupporting
confidence: 81%
“…16,19,22,23 It has been validated, and its popularity relates to its ease of use. No preoperative TESS results were available.…”
Section: Discussionmentioning
confidence: 99%